Simulation and experimental analysis of critical stress regions of deep-water annular blowout preventer. (December 2019) - Li, Wang; Tang, Yang; He, Yufa
Abstract: In deep-water drilling for oil and gas, the annular blowout preventer (BOP) is subjected to sustained high pressure or impact loads, causing the concentration of stress in some regions, which can easily cause cracks or fatigue damage. The top cover and housing of the annular BOP are the main pressure-containing parts. Once they fail during the emergency shut-in process, a blowout accident will occur, and there may be casualties and major economic losses. Therefore, the stress concentration regions of the top cover and the housing must be analysed to ensure safe operation. In this study, a high-fidelity approach to monitor the stress was established. This approach combines the theoretical calculation method (TCM), finite-element analysis (FEA) and stress testing experiment (STE). The stress distribution laws of the top cover and housing were measured under the rated working pressure and hydrostatic test pressure. The results indicated that the TCM, FEA, and STE exhibited the same curve trend of stress. Moreover, the FEA results were almost identical to the STE results for the stress values of testing points. The FEA results indicated that there were two critical stress regions in the housing. These were regions where cracks and failures had actually occurred in the past. The main technical contribution of the study is that it may serve as the basis for additional investigations into abandonment evaluation, fatigue analysis, and residual life evaluation. Highlights: A high-fidelity approach combining theoretical calculation method, finite element analysis and stress testing experiment. The stress distribution laws under rated working pressure and hydrostatic test pressure were analysed. Two critical stress regions of annular blowout preventer were determined.